2015
DOI: 10.1248/bpb.b14-00847
|View full text |Cite
|
Sign up to set email alerts
|

In a Methotrexate-Induced Model of Intestinal Mucositis, Olmesartan Reduced Inflammation and Induced Enteropathy Characterized by Severe Diarrhea, Weight Loss, and Reduced Sucrose Activity

Abstract: The aim of this study was to evaluate the effect of olmesartan (OLME), an angiotensin II receptor antagonist, on an intestinal mucositis model. Briefly, daily intraperitoneal (i.p.) injections of methotrexate (MTX) 7 mg/kg were administered to rats on 3 consecutive days. A subset of these rats was also pretreated with oral administration of OLME (0.5, 1.0, or 5.0 mg/kg) or vehicle as a control 30 min prior to MTX injection. Body weight, feces scoring, and death were recorded daily. On day 4, the rats were kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…Chang CT noted that the levels of proinflammatory cytokines, such as IL-1β and TNF-α, were elevated in the oral tissue with mucositis developed due to chemotherapy 8 . Another study shows that the levels of IL-1β and TNF-α were increased and inflammatory ulcers were developed in the intestinal tissue with MTX 3 . In this study, IL-1β and TNF-α gene expressions were significantly increased in the tissues in which MDA was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Chang CT noted that the levels of proinflammatory cytokines, such as IL-1β and TNF-α, were elevated in the oral tissue with mucositis developed due to chemotherapy 8 . Another study shows that the levels of IL-1β and TNF-α were increased and inflammatory ulcers were developed in the intestinal tissue with MTX 3 . In this study, IL-1β and TNF-α gene expressions were significantly increased in the tissues in which MDA was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Logan and colleagues demonstrated that IL-1β and TNF-α are increased in mucositis related to MTX and other chemotherapy medications [27]. de Araujo et al [28] stated that inflammation was developed in an MTX mucositis model where proinflammatory cytokines, such as IL-1β and TNF-α, were implicated. This information suggests that inflammation and oxidative stress developed due to MTX in the oropharyngeal tissue in our study.…”
Section: Discussionmentioning
confidence: 99%
“…MTX was reported to cause hyperemia, inflammatory cell infiltration and loss of villus epithelial cells in the small intestines of rats [6]. In another study, MTX has been reported to lead to the cellular loss, severe villus atrophy and PMNL leukocyte infiltration [7]. In addition to these histopathological findings, MTX is known to cause intestinal hemorrhage [18].…”
Section: Discussionmentioning
confidence: 99%